2018
DOI: 10.1111/nyas.13972
|View full text |Cite
|
Sign up to set email alerts
|

Provision of micronutrients in coexisting public health programs and risk of excessive intake: regulatory considerations

Abstract: Countries around the world have been implementing public health interventions to provide vitamins and minerals. There is a concern that the cumulative micronutrient contribution of coexisting programs, when targeting the same population, may exceed their safe levels of intake, thus potentially challenging the primum non nocere principle. We assessed the regulatory framework of such interventions and determined qualitatively whether there were provisions in the regulations that called for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Because of the concerns of several nutritional programs occurring in parallel without proper monitoring, some experts have conducted thorough reviews to map these efforts. For example, a 2019 review identified all the micronutrient programs occurring in Bangladesh, Chile, China, Costa Rica, Guatemala, Malawi, Uganda, and Zambia 62 . Similarly, a review of the SMILING project, a transnational collaboration between Cambodia, Indonesia, Laos PDR, Thailand, and Vietnam, with academic European partners from Europe, conducted a mapping of current fortification programs in these five countries 63 .…”
Section: Potential Weaknesses Of Multiple Simultaneous Micronutrientmentioning
confidence: 99%
“…Because of the concerns of several nutritional programs occurring in parallel without proper monitoring, some experts have conducted thorough reviews to map these efforts. For example, a 2019 review identified all the micronutrient programs occurring in Bangladesh, Chile, China, Costa Rica, Guatemala, Malawi, Uganda, and Zambia 62 . Similarly, a review of the SMILING project, a transnational collaboration between Cambodia, Indonesia, Laos PDR, Thailand, and Vietnam, with academic European partners from Europe, conducted a mapping of current fortification programs in these five countries 63 .…”
Section: Potential Weaknesses Of Multiple Simultaneous Micronutrientmentioning
confidence: 99%
“…This may be due, at least in part, to supplementation or fortification efforts. The Government of Malawi mandates various fortification programs: wheat flour and maize meal which are industrially processed are fortified with various vitamins and minerals, including folic acid, iron, zinc, and vitamin A, while sugar and cooking oil are also fortified with vitamin A (Mejia, Kuo, and Beltran-Velazquez 2019). Unfortunately, the IHS surveys do not collect enough information to take fortification into account in assessing the adequacy of nutrient intake.…”
Section: Nutrient Adequacymentioning
confidence: 99%
“…With regard to nutrient deficiencies, it highlights the need to reduce iron-deficiency anemia and eliminate vitamin B12, folate, and zinc inadequacies. Enforcing mandated micronutrient fortification is part of the Strategic Plan -industrially-processed wheat flour and maize meal are required to be fortified with folic acid, iron, zinc, and vitamin A, while sugar and cooking oil must be fortified with vitamin A (Mejia, Kuo, and Beltran-Velazquez 2019). In addition, micronutrient supplementation programs, particularly for children aged 6 to 24 months, are to be intensified as part of the public health efforts of government.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, overlap in consumption of multiple sources of fortified foods could put some groups at risk of exceeding the UL if program design (e.g., selection of fortification levels) does not account for this overlap. In practice it is challenging to adapt the design of public health programs to take into account these changes to the food system because often there is no mechanism for tracking the composition of voluntarily fortified products ( 56 ). In these scenarios with combined LSFF and fortified biscuits, we did not see evidence that biscuit fortification would contribute to intakes above the UL at the modeled fortification levels.…”
Section: Discussionmentioning
confidence: 99%